Access of non-specialist sexual health services by men who have sex with men: do they differ from those attending specialist services?. (25th November 2016) - Mebrahtu, Helen; Furegato, Martina; Sile, Bersabeh; Were, John; Mohammed, Hamish; Hughes, Gwenda
Abstract : Objectives: Men who have sex with men (MSM) bear a disproportionate burden of STIs. While routine STI surveillance data suggest MSM regularly access specialist genitourinary medicine (GUM) clinics for their sexual healthcare, the extent to which MSM attend non-specialist sexual health services (SHSs) is unclear. Methods: We used data from the GUM Clinic Activity Data Set (GUMCADv2), the national STI surveillance system, to compare the characteristics, service usage and STI outcomes of MSM accessing specialist and non-specialist (non-GUM) SHSs in England in 2014. Pearson's χ 2, Student's t-test and logistic regression analysis were used. Results: Where sexual orientation was recorded (92%), 11% (4552/41 597) of non-GUM attendances were among MSM compared with 28% (280 466/999 331) of GUM attendances (p<0.001). Compared with those attending GUM services, MSM attending non-GUM services were younger (mean age: 30.2 years vs 37.7 years; p<0.001) and were more likely to be of mixed ethnicity (4.9% vs 3.5%; p<0.001), to have had a full sexual health screen (chlamydia, gonorrhoea, syphilis and HIV tests) (48.0% vs 37.0%; p<0.001) and to be diagnosed with chlamydia (7.4% vs 4.1%; p<0.001) and gonorrhoea (8.5% vs 6.5%: p<0.001). MSM attending non-GUM services had slightly lower HIV test uptake (87.0% vs 95.0%; p=0.157) and were less likely to be diagnosed with HIV (0.5% vs 0.8%; p=0.019), compared with those attending GUM clinics. Conclusions: Non-specialist SHSs play an important role in the care of MSM and should ensure services meet their needs.